2022
DOI: 10.1001/jamanetworkopen.2022.36524
|View full text |Cite
|
Sign up to set email alerts
|

Association of Adequacy of Broadband Internet Service With Access to Primary Care in the Veterans Health Administration Before and During the COVID-19 Pandemic

Abstract: ImportanceAlthough telemedicine expanded rapidly during the COVID-19 pandemic and is widely available for primary care, required broadband internet speeds may limit access.ObjectiveTo identify disparities in primary care access in the Veterans Health Administration based on the association between broadband availability and primary care visit modality.Design, Setting, and ParticipantsThis cohort study used administrative data on veterans enrolled in Veterans Health Administration primary care to identify visit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Interestingly, differences in use of audio-only and video visits were noted even in the Veterans Health organization which has for years been using telehealth services to connect veterans with their providers. When comparing post-pandemic telehealth use between March 2020 and June 2021 to visits before February 2020, patients living in areas with poor broadband speed were less likely to use video telehealth after the onset of the COVID-19 pandemic ( 51 ). In second quarter of 2020, as in-person visits plummeted, approximately 1,750,000 primary care telephone encounters took place compared to around 150,000 video encounters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, differences in use of audio-only and video visits were noted even in the Veterans Health organization which has for years been using telehealth services to connect veterans with their providers. When comparing post-pandemic telehealth use between March 2020 and June 2021 to visits before February 2020, patients living in areas with poor broadband speed were less likely to use video telehealth after the onset of the COVID-19 pandemic ( 51 ). In second quarter of 2020, as in-person visits plummeted, approximately 1,750,000 primary care telephone encounters took place compared to around 150,000 video encounters.…”
Section: Resultsmentioning
confidence: 99%
“…COVID-19 itself helped highlight existing disparities in the United States healthcare system with Black, Hispanic, and Native Americans testing positive for and dying of COVID-19 at a higher rate than other racial and ethnic groups ( 70 ). Beyond this, researchers across the country repeatedly found that socioeconomic and demographic characteristics, rather than clinical factors, were predictive of whether patients used video or audio-only (phone) visits to connect with clinicians ( 12 , 41 , 48 , 50 , 51 , 71 ). Notably, across studies that looked at rural or diverse patient cohorts, rates of audio-only telehealth use were much higher than the 30% of visits that Center for Medicare & Medicaid Services (CMS) estimated were audio-only during the first years of the pandemic ( 72 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are important gaps in access to devices and broadband data (Zahnd et al, 2022). However, up to 81.6% of Americans have access to a smartphone (Flynn, 2023) and a nationwide mental health care organization-the Veteran's Administration-estimates that 93.3% of patients have at least adequate broadband (O'Shea et al, 2022). Second, due to self-selection, this sample may be more favorably predisposed toward AI technology than the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Census block groups were matched to FCC data. HSI (vs low-speed internet [LSI]) was defined as living in a census block group where the median block had a maximum available download speed of 940 megabits per second or higher according to the distribution of internet speed in our data and documented telehealth requirements for download and upload speed …”
Section: Methodsmentioning
confidence: 99%